Supervisi Manajerial dalam Meningkatkan Pelayanan Administrasi Pendidikan di SMA Negeri 1 Jonggat - Mohamad Tohar (Jurnal Paedagogy, 2022)
This study aims to describe managerial supervision in improving education administration services at SMAN 1 Jonggat, Central Lombok Regency. This research method uses a descriptive qualitative approach. The research subjects were the principal, vice principal of the curriculum section, vice principal of the public relations section, and the head of administration. Data collection techniques used are observation, interviews, and documentation. The data obtained were analyzed by presenting data, reducing data and drawing conclusions. Meanwhile, to obtain the validity of the data using source triangulation, technical triangulation, and time triangulation. The results of this study indicate that the implementation of managerial supervision at SMAN 1 Jonggat carried out by the principal and the head of administration in improving educational administration services includes program planning, organizing, implementing, and evaluating. The managerial supervision carried out has been carried out optimally so that it can improve administrative services and improve the quality of education in schools.